Cystic lesions and their mimics involving the intrahepatic bile ducts and peribiliary space: diagnosis, complications, and management. - Khot, Rachita; Ganeshan, Dhakshinamoorthy; Sundaram, Karthik M.; Depetris, Jena N.; Ludwig, Daniel R. (Abdominal Radiology, 2025)
Biliary and peribiliary cystic lesions represent a diverse group of abnormalities, often discovered incidentally during imaging for unrelated conditions. These lesions, typically asymptomatic, necessitate precise imaging modalities to characterize their nature and determine subsequent clinical actions, such as follow-up imaging, biopsy, or surgical referral. The anatomic location of these cystic lesions, whether biliary or peribiliary, influences both diagnostic and prognostic outcomes. Biliary cystic lesions, such as mucinous cystic neoplasms, intraductal papillary neoplasms of the bile duct, and Caroli disease, require careful monitoring due to their propensity to develop malignancy. In contrast, peribiliary cysts are often associated with chronic liver disease and may indicate disease progression through a gradual increase in cyst size. Accurate differentiation of these lesions from other clinical entities that have overlapping features on imaging, such as microabscesses, bilomas, Langerhans cell histiocytosis, neurofibromatosis, and vascular anomalies such as cavernous transformation of the portal vein, is essential given the divergent management for each. This article focuses on intrahepatic biliary and peribiliary cystic lesions and their mimics, highlighting their imaging characteristics with an emphasis on magnetic resonance imaging and magnetic resonance cholangiopancreatography, differential diagnosis, potential associated complications, and clinical management.